2018
DOI: 10.1002/mabi.201800127
|View full text |Cite
|
Sign up to set email alerts
|

A General Strategy for Extrusion Bioprinting of Bio‐Macromolecular Bioinks through Alginate‐Templated Dual‐Stage Crosslinking

Abstract: The recently developed 3D bioprinting technology has greatly improved the ability to generate biomimetic tissues that are structurally and functionally relevant to their human counterparts. The selection of proper biomaterials as the bioinks is a key step toward successful bioprinting. For example, viscosity of a bioink is an important rheological parameter to determine the flexibility in deposition of free-standing structures and the maintenance of architectural integrity following bioprinting. This requireme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 49 publications
0
32
0
Order By: Relevance
“…As a kind of derivation of modified extracellular matrix components, GelMA has superb biocompatibility, and thus, the GelMA anisotropic hydrogel SCPs were suitable for cell culture ( fig. S12) (40)(41)(42)(43). Similar to the pNIPAM anisotropic hydrogel SCPs, the resultant GelMA anisotropic hydrogel SCPs could also exhibit vivid colors ( fig.…”
Section: Resultsmentioning
confidence: 97%
“…As a kind of derivation of modified extracellular matrix components, GelMA has superb biocompatibility, and thus, the GelMA anisotropic hydrogel SCPs were suitable for cell culture ( fig. S12) (40)(41)(42)(43). Similar to the pNIPAM anisotropic hydrogel SCPs, the resultant GelMA anisotropic hydrogel SCPs could also exhibit vivid colors ( fig.…”
Section: Resultsmentioning
confidence: 97%
“…The different complementary network bioinks were printed using a tight range of process parameters, thus providing a generalized 3D printing methodology with broadened scope. Unlike the use of viscosity modifiers [e.g., alginate ( 20 ) and cellulose ( 21 , 22 )] that are retained in the bioprinted structure, the complementary network bioinks naturally release the majority of gelatin at 37°C. Critically, the inclusion of gelatin did not notably affect the mechanical properties of the hydrogels after thermal release, nor the ability of encapsulated chondrocytes and osteosarcoma cells to produce cartilaginous or mineralized tissue, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed, the viscosity of alginate is an important component to control when 3D bioprinting, it has been shown that a viscosity of 300-30,000 millipascal second (mPa•S) is optimal for printing, an alginate concentration of 2-4% provides this viscosity (He et al, 2016). Alginate can be printed effectively at a range of temperatures in order to achieve the required viscosity (He et al, 2016;Zhu et al, 2018). However, alginatebased hydrogels have been shown to be most effective at 37 • C due to: accurate extrusion flow rate, decreased occurrence of obstruction and compatibility with cell viability (Ding et al, 2018).…”
Section: Plant-derived Biomaterials Alginatementioning
confidence: 99%
“…Fabrication of tissue engineered aortic valve conduits using an alginate/gelatin polymer bioink has been successfully achieved using 3D bioprinting techniques. It was found that by direct encapsulation Duan et al, 2013;Malda et al, 2013;Dolati et al, 2014;Kundu et al, 2015;Li et al, 2015a;Markstedt et al, 2015;Zhang et al, 2015;Ansari et al, 2016;Daly et al, 2016;He et al, 2016;Nishimura et al, 2018;Park et al, 2018;Solovieva et al, 2018;Zhu et al, 2018 Nanocellulose Bhattacharya et al, 2012;Lou et al, 2014;Malinen et al, 2014;Li et al, 2015b;Markstedt et al, 2015;Rees et al, 2015;Torres-Rendon et al, 2015;Toivonen et al, 2016;…”
Section: Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation